Access to Justice: An Effective Pretrial Model to Guarantee the Right to Defense for Suspects in Indonesia - Susilo, Erwin; Din, Mohd; Suhaimi; Mansur, Teuku Muttaqin (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2025)
This paper examines the ineffectiveness of the pretrial mechanism in Indonesia in guaranteeing the right of suspects to submit and request examination of exculpatory evidence during the investigation stage. Although the Criminal Procedure Code (CPC) provides a legal basis for this right, no rules guarantee that investigators will conduct such examinations, as evidenced by several cases in which investigators ignored such requests. This study is normative legal research, employing a statutory, conceptual, and comparative approach. It compares the Brady Rule in the United States, which requires prosecutors to disclose evidence favorable to the defendant, and the Dutch model of the 'rechter-commissaris', which grants judges the authority to oversee investigative actions actively. The results of this study recommend expanding the authority of pretrial judges to order investigators to examine mitigating evidence based on requests from the suspect or their legal counsel. This reform is important to realize the principles of fair trial, favor defensionis, and equality of arms, as well as to strengthen constitutional protection of human rights and the values of Pancasila. Preliminary hearings, as conceptualized here, can address the injustices that remain unresolved despite decades since the enactment of the CPC in 1981.